2017
DOI: 10.1093/brain/awx255
|View full text |Cite
|
Sign up to set email alerts
|

Presence of tau pathology within foetal neural allografts in patients with Huntington’s and Parkinson’s disease

Abstract: Cell replacement has been explored as a therapeutic strategy to repair the brain in patients with Huntington's and Parkinson's disease. Post-mortem evaluations of healthy grafted tissue in such cases have revealed the development of Huntington- or Parkinson-like pathology including mutant huntingtin aggregates and Lewy bodies. An outstanding question remains if tau pathology can also be seen in patients with Huntington's and Parkinson's disease who had received foetal neural allografts. This was addressed by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 64 publications
3
40
0
Order By: Relevance
“…Vuono et al (2015) detected similar Tau deposits like perinuclear rings, flame-shaped and globular inclusions as well as astrocytic plaques in striatum and cortex of HD subjects but, in this case, with an antibody against phosphorylated Tau (AT-8). Similarly, in a more recent study, Cisbani et al (2017) also detected AT-8 positive neuronal inclusions-apart from NFTs and NTs-in striatum and cortex of HD patients.…”
Section: Tau-positive Cytoplasmic Aggregatessupporting
confidence: 60%
See 1 more Smart Citation
“…Vuono et al (2015) detected similar Tau deposits like perinuclear rings, flame-shaped and globular inclusions as well as astrocytic plaques in striatum and cortex of HD subjects but, in this case, with an antibody against phosphorylated Tau (AT-8). Similarly, in a more recent study, Cisbani et al (2017) also detected AT-8 positive neuronal inclusions-apart from NFTs and NTs-in striatum and cortex of HD patients.…”
Section: Tau-positive Cytoplasmic Aggregatessupporting
confidence: 60%
“…Using antibodies other than AT-8, an increase in Tau phosphorylation at Ser396/Ser404/Ser199 and Thr205 epitopes, while no changes in epitopes Ser235/Ser262/Ser356, has been observed in the putamen of a cohort of 56 patients (St-Amour et al, 2018). Recently, hyperphosphorylated Tau (detected with antibodies AT8, CP13, AT180b and PHF-1) has been detected in fetal tissue transplanted into cortex and striatum of two HD cases (Cisbani et al, 2017).…”
Section: Tau Phosphorylation In Hdmentioning
confidence: 99%
“…Similar phenomena were observed in mice injected with filament 4R-tau strains formed in HEK293T cells ( 41 ). Further, in patients with PD who received cell-replacement therapy to repair brain damage, hyperphosphorylated tau such as phospho-tau Ser202 and Thr205 were found in grafted neurons years after transplantation ( 42 ). Taken together, these findings demonstrate tau strain-specific prion-like transmission and spreading in the disease state, including in PD.…”
Section: Assembled Tau In Pdmentioning
confidence: 99%
“…Of note, protein inclusions in neurons, suggestive of Lewy pathology, have been found in fetal tissue grafts characteristic of PD . Recent studies have suggested that spreading of host‐derived tau may result in pathology in grafted tissue in both PD and HD patients …”
Section: Do Mhtt Aggregates Transfer To Transplanted Cell Grafts In Amentioning
confidence: 99%